2018
DOI: 10.1039/c7ta08781k
|View full text |Cite
|
Sign up to set email alerts
|

Platinum loaded tin dioxide: a model system for unravelling the interplay between heterogeneous catalysis and gas sensing

Abstract: The presented work unravels the complex structure–function-relationships of Pt-loaded SnO2, namely the sensitization by a Fermi-control mechanism and relation of catalytic activity and gas sensing effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 43 publications
3
74
0
1
Order By: Relevance
“…The DRIFTS spectra of both materials show that the reaction of CO is no longer taking place on the SnO2 surface and, thus, is shifted to the noble metal clusters. These findings suggest a sensitization by a Fermi-level control mechanism, as recently reported for Pt loaded SnO2 or Rh loaded WO3 [26,47].…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The DRIFTS spectra of both materials show that the reaction of CO is no longer taking place on the SnO2 surface and, thus, is shifted to the noble metal clusters. These findings suggest a sensitization by a Fermi-level control mechanism, as recently reported for Pt loaded SnO2 or Rh loaded WO3 [26,47].…”
Section: Resultssupporting
confidence: 85%
“…In humid air water vapor inhibits both reactions, but the inhibiting effect is stronger for the reoxidation and, thus, the sensor signals increase compared to dry air, while the catalytic activity of the material decreases [26]. A strong difference between the CH4 gas response of Au/SnO2 and Pd/SnO2 is observed.…”
Section: Pd-loaded Samplesmentioning
confidence: 91%
See 2 more Smart Citations
“…In order to gain fundamental insights on this topic, 0.5 and 1 at% Rh2O3-loaded In2O3, were chosen as model samples-the investigating approach is inspired by the work described in [1,2], because it was demonstrated that it helped the prevalence of a Fermi-level control mechanism that explained the gas sensing performance. Besides the loaded samples, an unloaded one was used as a reference; all sensors were operated at 300 °C.…”
Section: Introductionmentioning
confidence: 99%